2019
DOI: 10.1177/1753193419895160
|View full text |Cite
|
Sign up to set email alerts
|

Clinical tests for assessing the presence and quality of the palmaris longus tendon: diagnostic accuracy of examination compared with ultrasound

Abstract: Various clinical tests are used to evaluate the palmaris longus tendon, but their accuracy is unknown. We assessed the accuracy of clinical tests (Schaeffer’s, Thompson’s, Mishra-I, Mishra-II) against ultrasound as the reference standard. We hypothesized that Schaeffer’s was most accurate and that examination can reliably assess the palmaris longus tendon’s length. Ninety-six wrists were examined clinically and evaluated with ultrasound by radiologists who were blinded to examination results. We calculated dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
1
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(39 reference statements)
0
1
1
3
Order By: Relevance
“…In this study, Thompson's test showed the presence of 109 (79.6%) tendons in the right hand and 106 (77.4%) tendons in the left hand. Our study varies with the studies conducted by Kigera and Mukwaya 1 and Johnson et al 8 where Thompson's test detected tendons in 90.7 and 91%, respectively, of all the participants.…”
Section: Discussioncontrasting
confidence: 88%
“…In this study, Thompson's test showed the presence of 109 (79.6%) tendons in the right hand and 106 (77.4%) tendons in the left hand. Our study varies with the studies conducted by Kigera and Mukwaya 1 and Johnson et al 8 where Thompson's test detected tendons in 90.7 and 91%, respectively, of all the participants.…”
Section: Discussioncontrasting
confidence: 88%
“…O teste de Schaeffer detectou com precisão este tendão com > 90% de sensibilidade e especificidade. 30…”
Section: Discussionunclassified
“…The Schaeffer test accurately detected this tendon with > 90% sensitivity and specificity. 30 The studies to determinate the prevalence of absence of PLT present different amount of subjects avaluated. Alves et al, 17 In our study we obtained a PLT absence rate of 26.2%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PL varlığının belirlenmesinde referans alınan çok az standart test bulunmaktadır. Bu testlerle birlikte operasyon öncesi bulgular veya gelişmiş görüntüleme yöntemleri PL tendonunun varlığını veya yokluğunu göstermektedir (13). Literatürde PL varlığının de-ğerlendirilmesinde standart olan Schaeffer testi (12), Thompson testi (14), Mishra I testi ve Mishra II testi (15) ve Pushpakumar iki parmak belirtisini (16) testleri kullanılmaktadır.…”
Section: Introductionunclassified